2013
DOI: 10.1386/jaac.5.1.25_1
|View full text |Cite
|
Sign up to set email alerts
|

Reading as participatory art: An alternative mental health therapy

Abstract: This article outlines the health and well-being impacts of a specific community reading programme, ‘Get into Reading’, pioneered by The Reader Organisation, as demonstrated in a specific health context, Mersey Care NHS Mental Health Trust. The discussion broadly considers the historical positioning of this reading and health experiment, in terms of both mental health and arts-in-health developments and trends. The article also highlights some of the challenges and excitements of seeking to capture the health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…• Groups for Mersey Care NHS Trust service users, led by a trained Reader in Residence, and also training NHS staff to grow a lasting reading-group culture 7 .…”
Section: Therapeutically Relevant Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Groups for Mersey Care NHS Trust service users, led by a trained Reader in Residence, and also training NHS staff to grow a lasting reading-group culture 7 .…”
Section: Therapeutically Relevant Effectsmentioning
confidence: 99%
“…Billington and colleagues hypothesised that group reading should bring improvement in the areas of social, mental/ educational, and emotional/psychological wellbeing, and found qualitative evidence of improvements across all areas, including: enhanced concentration, interest in learning, self-awareness, and capacity for self-expression; increased confidence; reduced sense of isolation 2 . Similarly, the Mersey Care initiative, assessed in a Merseyside Service User Evaluation, documented 'improvements in confidence, self-esteem, self-expression, memory, concentration, creativity, social engagement, listening skills and overall health and well-being' 7 . Robinson 1 reported positive effects on mood, loss of self (being 'taken out of oneself'), concentration, confidence and self-esteem, pride and achievement, and communication skills, as well as appreciation of the opportunity to reflect on experiences in a supportive environment, and of a common purpose and shared 'journey'.…”
Section: Therapeutically Relevant Effectsmentioning
confidence: 99%
“…The writer Arnold Zable has reported that survivors of the “Black Saturday” bushfires responded positively to creative writing workshops, with one participant commenting, “I'm finding this more powerful than counseling” 1 . Projects like “Get into Reading,” used in prison communities, hostels for the homeless, and in mental health care by the Mersey Care NHS Trust (Billington et al, 2013 ). Encourage groups to read aloud together.…”
Section: Music and The Arts In Coping With Traumamentioning
confidence: 99%
“…The Liverpool City Region (LCR) also has a history of harnessing arts for mental health care through partnerships between arts and health providers. One NHS Foundation Trust, a provider of mental health services across North West England, has a strong track record of working with non-NHS agencies to encourage social inclusion and enable people to enhance their health and wellbeing by enriching their life experience (18)(19)(20)(21). Following the awarding of European Capital of Culture in 2008, the Trust in question nurtured a number of creative and cultural partnerships, which are now integral elements of the care offer.…”
Section: Introductionmentioning
confidence: 99%